(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article presents the results of a study devoted to the optimization of the clinical efficacy of complex therapy for children with exacerbation of IgE-mediated atopic dermatitis by including an immunomodulator of microbial origin - glucosaminylmuramyl dipeptide.